PENGARUH TINGKAT PERTUMBUHAN PERUSAHAAN, RETURN ON ASSETS (ROA), DAN SHAREHOLDER DISPERSION TERHADAP KEBIJAKAN DIVIDEN DAN INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA - Amanda Deby Sheviana; Tina Sulistiyani (Universitas Ahmad Dahlan, 2014)
This research aims to understand the influence of a variable degree growth of the company, return on assets (ROA) and shareholder dispersion partial evaluation and simultaneously to predict dividend policy to companies manufacturing industry which is listed on the Bursa Efek Indonesia. The sample collection by using purposive sampling method of sample and obtained 10 companies. The method of analysis data used a liniear regression analysis worship of idols with the level of significance 0.05. The research results show that: (1) the rate of growth of the company have a negative influence and significance 0.038. (2) ROA it has some positive effects and significance against its policies with a value of dividend t count 4,827 and value of significant 0,000. (3) shareholder dispersion have a negative influence and significant against its policies with a value of dividend t count -3,420 and value of significant 0.002. (4) the rate of growth of the company, return on assets (ROA), shareholder dispersion in together influential positive and significant for policies with the value of dividend f count 16,089 significance and value 0.000.